Net primary productivity, carbon sequestration and carbon stocks in areca-cocoa mixed crop system - Balasimha, D.; Kumar, S. Naresh (Journal of Plantation Crops, 2013)
Carbon sequestration by terrestrial biomass is one of the mitigation strategies reducing GHGs in the atmosphere. The areca-cocoa mixed crop not only ensures a sustainable crop production, but also serves as a good system for biomass production and carbon accumulation. Arecanut is grown either as mono-plantation or intercropped with other plantations like cocoa, banana, etc, whereas, cocoa is grown only as an intercrop of either coconut or arecanut. Areca-cocoa system had a standing biomass of 23.15, 54.09, 87.10 and 121.93 t ha-1 in 5th, 8th, 15th and 20th years of growth, respectively. Annual increments in biomass or net primary productivity ranged from 1.38-2.66 t ha-1 in cocoa and 3.34-7.11 t ha-1 in areca. Parallel to these, CO2 sequestration ranged from 2.02-3.89 and 5.14-10.94 in cocoa and areca respectively. The standing biomass increased over time indicating accumulation of biomass in stem and also due to increase in yield by arecanut and cocoa plants an age up to 20th year of planting. The study has thus revealed that the biomass and primary productivity is considerable with areca-cocoa mixed crop and comparable to any agro-forestry systems involving cocoa. Arecanut cocoa based cropping systems produce abundant biomass to qualify for carbon sequestration. In this paper, the net primary productivity in an arecanut-cocoa system in terms of biomass production, calculation by biomass models and carbon sequestration are discussed.